Artificial pancreas clinical trials: Moving towards closed-loop control using insulin-on-board constraints - Fushimi, Emilia (2018)
Artificial pancreas (AP) systems for people with type 1 diabetes (T1DM) combine the use of a smart insulinpump with a Continuous Glucose Monitor (CGM) and a control algorithm to improve the regulation ofglycaemia. Based on the extensive clinical evidence provided by the main research groups in the area, ahybrid control algorithm combining insulin meal boluses and glucose feedback action has been recentlyapproved. However, this sort of algorithms should be refined especially during the postprandial period.In turn, fully closed-loop control strategies have to be further developed. In either case, intensive in vivovalidation is necessary to ensure the viability of the proposed strategy as an effective method to treatT1DM patients. In this paper, a safety layer called SAFE loop [1] is reformulated to be employed duringclinical trials in two different ways: the time enable mode to gradually activate the closed-loop controlafter an insulin meal bolus in hybrid configurations; and the amplitude enable mode to activate the fullclosed-loop control as long as the insulin infusion does not exceed the conventional therapy to a givenextent. The SAFE module decides the activation of the controller as a function of a constraint on the insulinon board (IOB). In the case of the Time Enable, this results in the use of a constant restriction on the IOB,whereas in the amplitude enable it results in the use of a time-varying IOB constraint. Both operationmodes are evaluated in silico using broadly accepted high-order models and the results contrasted withthe ones obtained without the SAFE protection.